2001
DOI: 10.1105/tpc.13.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Expression Pattern of 1300 Arabidopsis Genes under Drought and Cold Stresses by Using a Full-Length cDNA Microarray

Abstract: Full-length cDNAs are essential for functional analysis of plant genes. Using the biotinylated CAP trapper method, we constructed full-length Arabidopsis cDNA libraries from plants in different conditions, such as drought-treated, coldtreated, or unstressed plants, and at various developmental stages from germination to mature seed. We prepared a cDNA microarray using ‫ف‬ 1300 full-length Arabidopsis cDNAs to identify drought-and cold-inducible genes and target genes of DREB1A/CBF3, a transcription factor that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
455
2
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 971 publications
(483 citation statements)
references
References 42 publications
18
455
2
8
Order By: Relevance
“…To tolerate cold stresses, plants develop multiple mechanisms, including the accumulation of cryoprotective molecules and proteins, alterations in membrane lipid composition, and primary and secondary metabolite composition, as well as changes in global gene and protein expression (Artus et al 1996;Gilmour et al 2000;Seki et al 2001;Cook et al 2004;Kaplan et al 2004;Maruyama et al 2009;Lissarre et al 2010). For example, temperate plant species promote the synthesis of cryoprotective molecules, such as soluble sugars, sugar alcohols, and low molecular weight nitrogenous compounds (Janská et al 2010).…”
mentioning
confidence: 99%
“…To tolerate cold stresses, plants develop multiple mechanisms, including the accumulation of cryoprotective molecules and proteins, alterations in membrane lipid composition, and primary and secondary metabolite composition, as well as changes in global gene and protein expression (Artus et al 1996;Gilmour et al 2000;Seki et al 2001;Cook et al 2004;Kaplan et al 2004;Maruyama et al 2009;Lissarre et al 2010). For example, temperate plant species promote the synthesis of cryoprotective molecules, such as soluble sugars, sugar alcohols, and low molecular weight nitrogenous compounds (Janská et al 2010).…”
mentioning
confidence: 99%
“…Osmotic stress in plants involves several interconnected molecular pathways that transmit signals and produce stress-response metabolites [73,74], and gene transcripts associated with signaling can be up-or down-regulated within minutes of stress induction [75,76]. As drought conditions continue, plants often have relatively low osmotic potential [77][78][79], heightened oxidative stress [80,81], and to reduce water loss to the extent possible, accumulations of osmolytes such as antioxidants, amino acids, carbohydrates, and inorganic ions, altering the attractiveness and nutritional value of the plant to herbivorous arthropods [68][69][70]82].…”
Section: Water Deficit or Drought Stressmentioning
confidence: 99%
“…By cDNA microarray analysis of 1300 Arabidopsis genes, Seki et al [31] reported a DEAD-box helicase gene (accession number AB050574) as a cold stress-inducible gene suggesting a new role of helicases in stress signaling [25], but it has not been characterized further.…”
Section: Arabidopsis Fl25a4 Helicasementioning
confidence: 99%